Pengaruh berbagai Asal Benih Induk dan Media Tanam terhadap Pertumbuhan Jambu Mete - Bambang Pujiasmanto; Pardono Pardono; Eddy Triharyanto; Puji Harsono; Sulandjari Sulandjari; Hery Widijanto; T D Sulistyo; Supriyono Supriyono; Wisnu Adi Nugraha Permana Putra (Perkumpulan Agroteknologi/Agroekoteknologi Indonesia, 2020)
Common problems in cashew tree development are low plant productivity caused by the use of unqualified seeds and limited knowledge of seed handling. This research was aimed to study the role of the mother tree on the growth of cashew seeds and study the seedling and growth of cashew trees in several planting media. The method used was Completely Randomized Design (CRD), consisting of two treatment factors and 4 replications. The first factor was the planting medium consists of 4 types: soil; soil: manure (2: 1); husk charcoal: manure (2: 1); soil: charcoal husk: manure (1: 1: 1). While the second factor was the origin of the seeds from the parent tree with fruit colors red, green, yellow, pink. The results showed that the planting soil medium was very significantly affected by increasing plant growth, namely plant height, number, and leaf area. The interaction between media and seed origin was not significantly affected plant growth. The best seed growth was found on soil media, plant height reaches 31.750 cm, number of leaves with 19 leaves, with an area of 48.437 cm2.